Analisis Kualitas Pelayanan di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sumba Barat Pasca Digitalisasi Tanda Tangan Elektronik dengan Metode Importance Performance Analysis - Desandri Wolla Gollu; Yulius Nahak Tetik; Karolus Wulla Rato (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This study aims to evaluate the quality of public services at the Department of Population and Civil Registration of West Sumba Regency following the implementation of digitalization through the use of electronic signatures. A quantitative approach was employed, with data collected through questionnaires distributed to 100 respondents. Data analysis was conducted using the Importance Performance Analysis (IPA) method to identify gaps between the level of importance and service performance. The results indicate that, overall, service quality can be categorized as fairly good, as reflected by performance levels that are relatively close to public expectations. However, several service attributes remain in the priority quadrant, particularly in terms of system usability, service stability, and accessibility. Meanwhile, attributes such as service speed, data security, and staff responsiveness demonstrate satisfactory performance and should be maintained. These findings suggest that the implementation of electronic signatures has improved service efficiency and effectiveness, although further improvements are still required, particularly in technical aspects and system usability. Therefore, continuous improvement efforts are necessary to enhance public service quality, making it more responsive and oriented toward user satisfaction.